Controlling Surface Hydrophobicity of Cellulose-Lignin Composite Coatings. Issue 2 (May 2018) - Mbiada, A. A. Younyia; Musa, S.; Richter, O.; Kneer, A.; Barbe, S.
In the first part of this study, lignin esters were prepared by acylating lignin with organic acid anhydrides containing short saturated chains of various lengths (C2 to C4). The prepared esters were then mixed at different ratios with cellulose acetate in order to produce hydrophilic cellulose-lignin composite coatings. The impact of the chain length and the ratio of lignin ester on the surface hydrophobicity of the coatings were determined by measuring contact angles with deionized water. The second part of this contribution was dedicated to the development of hydrophobic cellulose-lignin composite coatings with controlled surface hydrophobicity. For this purpose, cellulose oleate and lignin oleate were both prepared by acylating cellulose and lignin with oleyl chloride (C18:1). Contact angles up to 175° were measured at the surface of the prepared coatings and a technical approach for the control of surface hydrophobicity was presented. Finally, a process for the manufacture of hydrophobic cellulose-lignin composite coatings was designed. Polymers involved in this process are exclusively derived from renewable resources (Wood & High Oleic Sunflower Oil).